Sistem Komunikasi dan Model Penyebaran Informasi Masyarakat Negeri Hitu, Kecamatan Leihitu, Kabupaten Maluku Tengah - Antasari Bandjar (CV. Syntax Corporation Indonesia, 2020)
The dissemination of strategic information about development and social change is a very important process in achieving developmental goals, thus identifying and utilizing various social communication institution for this purpose is necessary. This research aims to identify social communication institution employed by society in Negeri Hitu that can be used as media for effective and efficient information dissemination. The method used in this research is qualitative perspective and in depth interview. The key informants in this research are Raja Negeri Hitu, Secretary of Negeri Hitu, The head of Custom Board and his secretary, Saniri (the head of the village) and the head of youth community organization. The data obtained will be reduced, analyzed, and presented in the form of narration. This research shows that social cultural system really influences its communication system.